Effect of Different Concentrations of Aqueous Leaf Extracts of Some Plants on the Germination and Seedling Growth of Maize, Z. mays L. and Wheat (T. aestivum L.) - Khan, Rizwan Ali; Iqbal, Kaiser; Hussain, Aatif; Azeem, Showkat (International Journal of Environment, 2014)
Allelopathic effect of aqueous leaf extract of three different species (eucalyptus, guava, and litchi) were used to investigate their effect on germination, shoot and root lengths of two food crops viz. Zea mays L. (Maize) and Triticum aestivum (Wheat). Mature fresh leaves of three species were crushed and soaked for 24h; the filtrates were diluted to make different concentrations (T1 = 0.5%, T2 = 1.0%, T3 = 1.5%, T4 = 2.0%, and T5 = 0.0%), and were used to investigate their effect on the tested crops. The aqueous leaf leachate of three species was found to have inhibitory effect on germination, shoot, and root elongation on the tested crops. Current study indicates that inhibitory effect was much more pronounced at higher concentrations, and the effect increased with the increase in concentration. Among trees, Eucalyptus has much more effect on the tested crops than other species. DOI: http://dx.doi.org/10.3126/ije.v3i3.11085 International Journal of Environment Vol.3(3) 2014: 264-274